Conversion of spent mushroom sawdust substrate to simple sugars for bioethanol production / Soo Ching Siew - Soo, Ching Siew (2011)
Spent Mushroom Sawdust Substrate (SMSS) was appraised for its potential as a lignocellulosic waste source for conversion of to bioethanol. Aqueous perchloric acid is used to hydrolyze the lignocellulosic waste feedstock to simple sugars which are then fermented to ethanol. Aqueous perchloric acid was chosen as the medium for conversion of SMSS to sugars as it can hydrolyze the recalcitrant cellulosic biomass to give a significant amount of glucose without the need for strong heating or the application of pressure. The products of the breakdown of SMSS by perchloric acid were analysed by HPLC, glucometer and by Fehling’s method. HPLC results showed the presence of glucose and xylose. The sugars obtained were then fermented by the yeast, Saccharomyces cerevisiae, to yield ethanol. The products obtained from the fermentation were analysed by GC and results show the presence of ethanol and methanol. Some performance parameters for the production of bioethanol such as concentration of perchloric acid and the time of hydrolysis of SMSS were reported. The judicious use of the concentration of perchloric acid was important in order to control the reaction so that it leads to a minumum concentration of inhibitors and the maximum concentration of glucose. A conversion yield of of SMSS up to 12.3% was obtained. This translates to 1L of bioethanol produced for every 22.4 kg of the dried substrate.